2009
DOI: 10.2320/matertrans.md200809
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Strain Rate Dependence of Flow Stress in Severely Deformed Copper by Accumulative Roll Bonding

Abstract: Tensile tests and strain rate jump tests have been carried out at low temperatures (77 K $ room temperature (RT)) using pure Cu specimens that were severely deformed by accumulative roll bonding (ARB). The dependence of the flow stress on the temperature and the strain rate has been investigated and the strain rate sensitivity m and its variation caused by the change in the ARB cycle N are discussed. At RT, the strain rate sensitivity for N 4 stays at about 0.005. However, for N ! 5, m increases with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 29 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…In addition, it has been reported that, in severally deformed Cu, the activation volume exhibits an inverse dependence on temperature. The activation volume in Cu subjected to SPD decreases with temperature, while in coarse-grained Cu, it increases [6,8]. This peculiar behaviour of the activation volume in severely deformed Cu can be explained by a model according to which the activation process of dislocations in severely deformed Cu is different from that in coarse-grained Cu.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, it has been reported that, in severally deformed Cu, the activation volume exhibits an inverse dependence on temperature. The activation volume in Cu subjected to SPD decreases with temperature, while in coarse-grained Cu, it increases [6,8]. This peculiar behaviour of the activation volume in severely deformed Cu can be explained by a model according to which the activation process of dislocations in severely deformed Cu is different from that in coarse-grained Cu.…”
Section: Introductionmentioning
confidence: 82%
“…In order to determine the change in the activation volume from Equation (8), the strain-rate jump tests were performed for a greater number of temperatures between those shown in Figure 2. Figure 6 shows the temperature dependence of the activation volume as determined from Equation (8). Although a number of values have been suggested for the Taylor factor [14][15][16][17], M was taken as 2 in this study under the assumption that there should be a slip system with a Schmid factor of nearly 0.5, because of the large number of slip systems in bcc structures [15].…”
Section: Resultsmentioning
confidence: 99%
“…Examples include the extra-hardening phenomenon, with reported yield strengths greater than those predicted by the Hall-Petch curve, 8,9) the yield drop of face-centered cubic (FCC) metals that are not seen for CG materials, 9) greater variations in the strain rate with temperature in comparison to CG materials, [10][11][12][13][14] a hardening by annealing/softening by deformation effect 15) and an abnormal temperature dependence of the activation volume. 16) In order to nd practical applications for NC materials, the appearance of each of these phenomena must be explained, even though there is only a limited understanding of these causes of appearance at present. It has been proposed that the behavior of dislocations during the plastic deformation of NC materials will be different from that in CG materials [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the characteristic mechanical properties are the higher strain-rate sensitivity of flow stress and the decrease in activation volume for the ARB processed Cu when N ² 6. 16,17) The changes of the mechanical properties occur when ultrafine-grained structure appears in the specimens and this suggests the difference in the deformation mechanisms between materials with deformation structure and ultrafinegrain structure. The similarities of the strength and microstructure between the ARB processed single crystals and polycrystals when N ² 6 mean that grain boundaries in Cu before ARB do not affect the critical number of the ARB cycle N = 6, required to form ultrafine-grain structure showing characteristic mechanical properties.…”
Section: Discussionmentioning
confidence: 99%